Maintenance management system for upstream operations in oil and gas industry: a case study - Wan Mahmood, Wan Hasrulnizzam; Ab Rahman, Mohd Nizam; Md Deros, Baba; Mazli, Husiah (Inderscience Publishers, 2011)
This paper explores the plant maintenance management system that has been used by a giant oil and gas company in Malaysia. The system also called as PETRONAS maintenance management system (PMMS) used to manage the upstream operations for more than 100 plants of the case study company. Moreover, from the observations, focus group discussion with PMMS personnel and application through simulation (SAP R/3), this paper reviews the step-by-step approach and the elements that required for the PMMS. The findings show that the PMMS integrates the overall business strategy in upstream operations that consist of asset management, work management and performance management. In addition, PMMS’s roles are: to help operations personnel organise and plan their daily activities, to improve productivity and reduce equipment downtime, and to help operations management analyse the facilities and create performance and to provide and maintain the operational effectiveness of the facilities.